Picture Storybook Media on the Traditional Food “Amplang” from North Penajam Paser Regency to Improve Procedural Text Writing Skills for Fourth-Grade Elementary School Students - Sopian; Wahyu Suartiningsih; Nurul Istiq’faroh (LingPoet: Journal of Linguistics and Literary Research, 2026)
This study aims to analyze the use of picture storybook media based on the traditional food Amplang from North Penajam Paser Regency in improving procedural text writing skills of fourth-grade elementary school students. A qualitative descriptive method was employed. Data were collected through in-depth interviews, classroom observation, and documentation of student writing samples at SDN 023 Penajam. Analysis was conducted on the content, language, illustration, and curriculum alignment components of the picture storybook. The findings indicate that the Amplang picture storybook demonstrates high alignment with the Indonesian Language Learning Achievement for Phase B in the Merdeka Curriculum, incorporates contextual local wisdom values of North Penajam Paser, and presents illustrations that support students’ understanding of procedural text structure. The book is deemed feasible and relevant as a contextual literacy medium based on local wisdom that can facilitate the improvement of procedural text writing skills among fourth-grade elementary school students.